The Effect of Savings Growth, Deposit Growth, and Credit Growth on Profitability Growth - PUTRA, I Wayan Gde Yogiswara Darma; VIDYANTARI, Putu Kemala (International Journal of Environmental, Sustainability, and Social Science, 2023)
This research is entitled The effect of savings, deposits, and credit growth on profitability growth in LPD Kintamani District, Bangli Regency for the 2020-2022 period. The formulation of the problem in this study is whether savings growth, deposit growth, and credit growth affect profitability growth. This study aims to empirically examine the effect of savings growth, deposit growth, and credit growth on profitability growth. The population in this study included 60 LPDs in Kintamani District. The sample in this study was 54 LPDs determined based on the purposive sampling method. The types of data used are quantitative data and secondary data. The data analysis techniques used are classical assumption test, multiple linear regression analysis, f test, t test and determination coefficient. The results showed that savings growth had a significant positive effect on profitability growth while deposit growth and credit growth had an insignificant effect on profitability growth in LPD Kintamani District.